(untitled) (Bangladesh Veterinarian, 2024)
The effect of ovarian phase on oocyte quality in slaughterhouse material of cows was studied. Cumulus-oocyte complexes (COCs) were aspirated from all visible follicles. COCs were graded on the number and intensity of the cumulus cells and the homogeneity of the ooplasm as A (4 – 5 layers compact cumulus with a homogeneous ooplasm), B (1 - 2 layers compact cumulus with homogeneous ooplasm having a coarse appearance), C (slightly expanded cumulus with irregular cluster ooplasm), and D (denuded oocyte or expanded cumulus, irregular ooplasm). The overall aspiration rate of COCs was 37.2%. The aspiration rate was significantly higher (P<005) in follicular (41.2%) than in luteal phase (28.6%). The percentage of grade A and B oocytes was significantly (P<005) higher in the follicular phase (20.4 and 28.6%) than luteal phase (11.1 and 22.2%). The proportion of grade A COCs in the indigenous cows was significantly (P<005) higher (29.0%) than in crossbred cows (8.3%). Ovaries with diameter of 2.0 cm or more had higher proportion (P<005) of grade A and B COCs than others. It is suggested that follicular phase of the sexual cycle had significant effect on COCs quality. Bangl. vet. 2023. Vol. 40, No. 1-2, 1–7